A Bibliometric Analysis of the Use of Augmented Reality in Ethnomathematics Education - Ratu Mauladaniyati; Sumarni Sumarni (Journal of Emerging Technologies in Ethnomathematics, 2025)
One area that has been gaining increasing attention is the integration of Augmented Reality (AR) technologies in mathematics education, especially within the context of ethnomathematics. This study aims to explore trends, developments, and directions of research related to the use of Augmented Reality (AR) technology in ethnomathematics education through a bibliometric approach. By utilizing the Scopus database, relevant scientific articles were selected based on keywords such as "augmented reality", "ethnomathematics", and "education" from the Google Scholar database between 2015 and 2025. Publish or perish software was used to collect data while the Vosviwer application was applied to analyze the data. Using descriptive and bibliometric analysis, this study addresses two research problems as follows: a) the growth trajectory of studies related to the use of Augmented Reality (AR) technology in ethnomathematics; and b) mapping studies to identify the most important themes and topics. The results of the analysis show that the trajectory of studies related to the use of Augmented Reality (AR) technology in ethnomathematics. Several topics that are rarely studied are recommended to be basic ideas in further research. These findings contribute not only to mathematics education researchers but also to other stakeholders, including education policy makers.